The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1989
DOI: 10.1111/j.1365-3091.1989.tb00611.x
|View full text |Cite
|
Sign up to set email alerts
|

Early Cambrian reefs, reef complexes, and associated lithofacies of the Shackleton Limestone, Transantarctic Mountains

Abstract: The Shackleton Limestone formed a carbonate platform that bordered part of the Greater Antarctic craton in middle and late Early Cambrian time. In the Holyoake Range of the central Transantarctic Mountains, this unit records deposition on a stable shelf on which flourished ecological reefs composed of microorganisms and archaeocyathans. Burrow‐mottled lime mudstone, wackestone and packstone with patch reefs represent accumulation in shelf areas of relatively low to moderate energy. Thick ooidal grainstone unit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(36 citation statements)
references
References 19 publications
0
36
0
Order By: Relevance
“…Synthesis of trilobite collections from the Shackleton by Palmer & Rowell (1995) has shown that they range from basal Atabanian through Botomian, and questionally into the Toyonian. It is generally agreed that the Shackleton Limestone was deposited on a shallow-water carbonate shelf or platform with minor terrigenous components, emergent in part, and populated by archaeocyathan bioherms (Laird 1963;Laird et al 1971;Burgess & Lammerink 1979;Rees et al 1989;Myrow et al 2002;Stump et al 2002a). However, before this study, a stratigraphy for the Shackleton Limestone had not been recognised.…”
Section: Introductionmentioning
confidence: 99%
“…Synthesis of trilobite collections from the Shackleton by Palmer & Rowell (1995) has shown that they range from basal Atabanian through Botomian, and questionally into the Toyonian. It is generally agreed that the Shackleton Limestone was deposited on a shallow-water carbonate shelf or platform with minor terrigenous components, emergent in part, and populated by archaeocyathan bioherms (Laird 1963;Laird et al 1971;Burgess & Lammerink 1979;Rees et al 1989;Myrow et al 2002;Stump et al 2002a). However, before this study, a stratigraphy for the Shackleton Limestone had not been recognised.…”
Section: Introductionmentioning
confidence: 99%
“…The bioconstr uctional capacity of archaeocyaths has been documented in many recent works, representing all regions and spanning their appearance in the Tommotian to their virtual demise in the Toyonian (ZhurAvlevA, 1960b(ZhurAvlevA, , p. 59, 1966(ZhurAvlevA, , 1972aJAmes & KobluK, 1978;JAmes & KlAPPA, 1983;gAnDin & Debrenne, 1984roWlAnD, 1984;roWlAnD & gAngloFF, 1988;Debrenne, gAnDin, & roWlAnD, 1989;JAmes, KobluK, & KlAPPA, 1989;rees, PrATT, & roWell, 1989;JAmes & grAvesTocK, 1990;Debrenne, gAnDin, & ZhurAvlev, 1991;KennArD, 1991;Kruse, 1991b;WooD, ZhurAvlev, & chimeD Tseren, 1993;Kruse, ZhurAvlev, & JAmes, 1995;riDing & ZhurAvlev, 1995;Kruse & others, 1996;ZhurAvlev, , 2001cWooD, 1999;coPPer, 2001;PrATT & others, 2001;roWlAnD & shAPiro, 2002;Kiessling, Flügel, & golonKA, 2003). The resultant bioconstructions (meterscale mounds) all had the same basic plan and can be categorized into component domains occupied by associations of lime mud, archaeocyaths, renalcid calcimicrobes, and/or cement.…”
Section: Bioconstructionmentioning
confidence: 99%
“…Reefs were either dominantly renalcid calcimicrobial or (rarely) dominated by metazoans (ZAmArreño, 1977;gAnDin & Debrenne, 1984;selg, 1986;sTePAnovA, 1986;Debrenne, gAnDin, & roWlAnD, 1989;rees, PrATT, & roWell, 1989;Debrenne & grAvesTocK, 1990;JAmes & grAvesTocK, 1990;WooD, ZhurAvlev, & chimeD Tseren, 1993;moreno-eiris, 1994). Indeed, historically, Tommotian archaeocyaths initially invaded purely calcimicrobial reefs, which had first proliferated in the preceding basal Cambrian NemakitDaldynian stage.…”
mentioning
confidence: 99%
“…The overlying Byrd Group is of lowermost Paleozoic age and is generally thought to unconformably overlie the Goldie Formation (Laird et al 1971;Stump 1995). The carbonate-ramp deposits of the Lower Cambrian Shackleton Limestone (Rees et al 1989) is the oldest unit, and its age is constrained by trilobite and archeocyathan fauna (Debrenne and Kruse 1986;Palmer and Rowell 1995). A number of siliciclastic units overlie the Shack-FIG.…”
Section: Stratigraphy and Depositional Historymentioning
confidence: 99%